Intercontinental translatability of a peer-led GP education model from New Zealand to the UK: a pilot study - Ben Hudson; Matthew Walmsley; Susan Bidwell; Louise Kennedy (BJGP Open)
Background: Pegasus Small Group education for GPs is a professional development programme that has been delivered in Canterbury, New Zealand for over 30 years. Peer-developed content is delivered in small groups supporting interactive discussions informed by evidence and locally relevant data. Aim: An international collaboration between South Tyneside Clinical Commissioning Group in the UK and Pegasus Health in Canterbury, New Zealand aimed to determine whether the Canterbury model of Small Group professional development for GPs was transferrable to the South Tyneside context. Design & setting: This was a pilot qualitative study testing proof of concept for the Pegasus Small Group GP education model of professional development in another country. Method: To test the concept, three pilot sessions on persistent pain, screening, and optimising treatment were delivered between November 2021 and March 2022. Four UK GPs were trained as Small Group leaders, and a member of the Pegasus team liaised with various UK GPs in South Tyneside to adapt topics for the local context. The use of videoconferencing (Microsoft Teams and Zoom) to deliver support, training, and the programme itself had been developed and refined during the COVID-19 pandemic, so that it could be run entirely online without losing its core components or interactive nature. Results: Of the 68 registered GPs, 31, 50, and 61 GPs attended the three sessions, respectively, 90% of whom rated the overall quality as good or excellent. These results and other positive feedback from attendees provided a mandate for a further extension of the programme over the following months. Conclusion: The pilot proved the potential for health systems to collaborate globally despite geographical distance. A wider evaluation to assess the impact of the education initiative is needed to determine the impact on patient care and to demonstrate the benefits of supporting the small group peer education model.